Point-of-contact interactive record linkage (PIRL) between demographic surveillance and health facility data in rural Tanzania - Christopher T. Rentsch; Georges Reniers; Chodziwadziwa Kabudula; Richard Machemba; Baltazar Mtenga; Katie Harron; Paul Mee; Denna Michael; Redempta Natalis; Mark Urassa; Jim Todd; Basia Zaba (International Journal of Population Data Science, 2017)
Introduction. Health and demographic surveillance systems (HDSS) have been an invaluable resource for monitoring the health status of populations, but often contain self-reported health service utilisation, which are subject to reporting bias.